1998
DOI: 10.1159/000052699
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependence in Prosimian Locomotion and Its Implications for the Distribution of Body Mass

Abstract: The mechanical requirements for arboreal life are reviewed and the constraints which these requirements impose on the body of a prosimian are defined. The mechanical necessities can be fulfilled only by animals which possess the appropriate morphological characters. It is incorrect to refer to these morphological traits directly as ‘adaptations’. Instead their a priori existence must be considered as the precondition for the acquisition of a certain life-style. Once such a life-style has been acquired, a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Common chimpanzees, bonobos, and modern humans differ considerably in body proportions (relative leg masses, muscularization, distribution of mass over the leg segments; Zihlman, 1984;Kano, 1992;Preuschoft et al, 1998) and in posture (erect vs. bent-hip/bent-knee walking; e.g., Crompton et al, 1998;Li et al, 1996). However, our results suggest that these differences do not greatly affect the overall dynamics of the oscillating legs (reflected in the spatio-temporal gait characteristics) during bipedal walking.…”
Section: Comparisons With Common Chimpanzees and Humansmentioning
confidence: 59%
“…Common chimpanzees, bonobos, and modern humans differ considerably in body proportions (relative leg masses, muscularization, distribution of mass over the leg segments; Zihlman, 1984;Kano, 1992;Preuschoft et al, 1998) and in posture (erect vs. bent-hip/bent-knee walking; e.g., Crompton et al, 1998;Li et al, 1996). However, our results suggest that these differences do not greatly affect the overall dynamics of the oscillating legs (reflected in the spatio-temporal gait characteristics) during bipedal walking.…”
Section: Comparisons With Common Chimpanzees and Humansmentioning
confidence: 59%
“…Biomechanical studies on leaping in primates have mostly focused on specialized leapers from the primate sub-order Strepsirrhini (nontarsier prosimians), particularly the Lemuridae, Indriidae, and Galagidae. Such studies (including: Demes and Gü nther, 1989;Preuschoft et al, 1996;Aerts, 1998;Preuschoft et al, 1998;Crompton and Sellers, 2007) have revealed functional relationships between leaping performance, body mass and segment length in primates.When leaping, larger animals are limited by muscle force, since force is proportional to length squared while mass is proportional to length cubed (see Alexander et al, 1981;Demes and Gü nther, 1989;Gü nther, 1989), and tend to minimize bone stresses by adopting shorter segments and smaller load arms (Biewener, 1989;Preuschoft et al, 1998;Scholz et al, 2006). Indeed, Demes et al (1999) demonstrated that while take-off forces are higher in larger animals, relative forces decrease with increasing body size.…”
mentioning
confidence: 99%
“…Indeed, Demes et al (1999) demonstrated that while take-off forces are higher in larger animals, relative forces decrease with increasing body size. Smaller animals, however, require maximization of impulse (force 3 time) to reach the required take-off velocity and so possess long distal segments to facilitate longer contact times at take-off (Preuschoft et al, 1998). Remarkably, despite a particularly forelimb-dominated locomotor repertoire, gibbons actually have long hind limbs in comparison to other nonhuman ape species (Schultz, 1936; Jungers, 1985), which could be particularly adaptive to maintaining contact with the compliant, deflecting branches, from which 67%-85% of gibbon leaps are performed (Fleagle, 1976;Gittins, 1983;Sati and Alfred, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adult shape is therefore reached through differential growth patterns of individual skeletal elements. These skeletal growth patterns must meet functional demands [Humphrey, 1998;Wells et al, 2002] that may change with increases in size [Preuschoft et al, 1998]. Studies of hominoids indicate that function may be more important than phylogeny in determining growth patterns, since suspensory apes exhibit ontogenetic similarities, as do knucklewalkers, despite their phylogenetic affinities [Jungers & Cole, 1992].…”
Section: Introductionmentioning
confidence: 99%